The Geobiology and Ecology of Metasequoia - LePage, Ben A.; Williams, Christopher J.; Yang, Hong.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The plant fossil record provides evidence that the genus Metasequoia was widely distributed and experienced a wide range of climatic and environmental conditions throughout the Northern Hemisphere from the early Late Cretaceous to the Plio-Pleistocene. Today the genus is limited to one species with approximately 5,000 mature individuals growing in the Xiahoe Valley in southeastern China. This book is a distillation of the collective efforts and results of the world's Metasequoia specialists and enthusiasts. It is the most up-to-date and comprehensive reference source for the genus and the authors have sought to incorporate obscure, hard-to-get and non-English reference sources. The book reviews what is known about the biology, ecology and physiology of fossil and living Metasequoia, current research directions and problems that remain unresolved. This book presents a definitive overview of fossil and living Metasequoia and was written by sixteen of the world's experts on this important genus. Given the reality of increasing human pressure and the inevitability of global change, efforts to conserve this ancient genus are underway.
and History -- The Evolution and Biogeographic History of Metasequoia -- Paleoecology and History of Metasequoia in Japan, with Reference to its Extinction and Survival in East Asia -- A High-Resolution Palynological Analysis, Axel Heiberg Island, Canadian High Arctic -- Metasequoia in the Oligocene Bridge Creek Flora of Western North America: Ecological Implications and the History of Research -- Gunther's Travels: The Odyssey of Metasequoia Seeds from the 1920s? -- Cuticle, Ultrastructure and Biomolecules -- Cuticle Analysis of Living and Fossil Metasequoia -- Ultrastructural Preservation in Middle Eocene Metasequoia Leaf Tissues from the Buchanan Lake Formation -- Biomolecules from Living and Fossil Metasequoia: Biological and Geological Applications -- Ecology and Ecophysiology -- Ecological Characteristics of Metasequoia glyptostroboides -- Physiological Ecology of Metasequoia glyptostroboides Hu et Cheng -- Competitive Advantages of Metasequoia in Warm High Latitudes -- Cultivars and Horticulture -- Selecting and Propagating New Cultivars of Metasequoia -- Cultivars of Metasequoia glyptostroboides -- A Conservation Plan for Metasequoia in China.
Keywords: LIFE SCIENCES; PALEONTOLOGY; TREES; ECOLOGY; LIFE SCIENCES; BIOGEOSCIENCES; GEOECOLOGY/NATURAL PROCESSES; PALEONTOLOGY; TREE BIOLOGY